Participant Reaction Assessment of Office Administration Training at Unit Pelaksana Teknis Balai Latihan Kerja (UPT BLK) Dinas Ketenagakerjaan Kota Bandung Based on Kirkpatrick's Level 1 Model - Griselda, Sarah; Kurniati, Tetty (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2024)
Training evaluation is a critical phase in the execution of any training program. The primary objective of training evaluation is to assess the overall success, effectiveness, and efficiency of the training program. This study aims to design, implement, and report on the evaluation of the Office Administration Training using the Kirkpatrick Model Level 1 (Reaction) at the UPT BLK Dinas Ketenagakerjaan Kota Bandung which has not been previously conducted. A quatitative research method was employed, with data collected through questionnaire with some necessary interviews. The data were analyzed to develop a Kirkpatrick Level 1 (Reaction) evaluation questionnaire, focusing on three aspects: (1) instructors/presenters, (2) training materials, and (3) training facilities, rated on a Likert scale from 1 to 4. The evaluation results revealed delays in instructor/presenter attendance and material delivery, as well as discomfort with the lighting facilities and poor internet access. This study underscores the need for improvements in the aspect of instructors/presenters and facilities at the UPT BLK Dinas Ketenagakerjaan Kota Bandung to ensure the success of future training programs.